Texas Hellions - Sharpe, Jon (Sharpe, Jon. Renegade rifles., 2010)
Skye Fargo teams up with a sharpshooting ten-year-old boy to rescue the prodigy's cousin, who was recently sold into slavery down in deadly Henders Gap.